Childhood Environmental Instability and Social-Emotional Outcomes in Emerging Adults. Issue 7 (April 2022) - Babad, Sara; Zwilling, Amanda; Carson, Kaitlin W.; Fairchild, Victoria; Nikulina, Valentina
Adverse childhood experiences (ACEs) can negatively affect social-emotional functioning. The association between individual and cumulative ACEs and social-emotional domains of self-esteem, loneliness, and negotiation in intimate partner relationships has not been explored in low-risk emerging adults, a gap this study aims to fill. An online survey was administered to undergraduate emerging adults, ages 18 to 25 years ( M age = 19.73, SD = 1.83; N = 436; 20.60% Hispanic; 63.80% female). The ACEs Survey, Child Abuse Potential Inventory, and Conflict Tactics Scale–2nd Edition were used. Three multivariate ordinary least squares regressions were run, each including predictors significant in bivariate analyses and outcomes of self-esteem, loneliness, and negotiation for each regression. Emotional abuse, B = −.20, p < .01; emotional neglect, B = −.21, p < .001; and substance using family member, B = −.12, p < .05, were negatively associated with self-esteem; emotional neglect, B = .11, p < .01, and cumulative ACEs, B = .16, p < .01, were positively associated with loneliness; and incarcerated family member was positively associated with negotiation, B = .12, p < .05. Overall, these findings suggest that individual ACEs associated with environmental instability (e.g., emotional abuse) are strong predictors of social-emotional outcomes, relative to ACEs associated with more direct physical harm (e.g., sexual abuse).